External Finance for Low-Income Countries. (International Monetary Fund, 1997)
Edited by Zubair Iqbal and Ravi Kanbur, this volume consists of papers presented at a joint IMF and World Bank conference on external financing for low-income countries. The primary focus was on the impact of external indebtedness on low-income countries, mainly in sub-Saharan Africa, the HIPC Debt initiative, the determinants and role of private capital flow, policies that could be implemented to catalyze private capital flows, and the appropriate role for official finance in the period ahead.